For ethnography / Paul Atkinson. - Atkinson, Paul, 1947- (SAGE, 2015)
This major book from one of the world's foremost authorities recaptures the classic inspirations of ethnographic fieldwork in sociology and anthropology, reflecting on decades of methodological development and empirical research. It is part manifesto, part guidance on the appropriate focus of the ethnographic gaze.